Analisis Pengaruh Inflasi, Jumlah Uang Beredar dan Suku Bunga terhadap Ekspor di Indonesia - Martina Br. Sinaga; Rinaldi Syahputra; Ahmad Ridha (MAN 4 Kota Pekanbaru, 2026)
Exports play an important role in promoting economic growth by generating foreign exchange earnings and strengthening international trade. However, Indonesia’s export performance has fluctuated considerably due to changes in macroeconomic conditions. This study examines the short-run and long-run effects of inflation, money supply (M2), and interest rates on Indonesia’s exports during the 2015–2024 period. Secondary time-series data were obtained from Statistics Indonesia (BPS) and Bank Indonesia (BI) and analyzed using the Vector Error Correction Model (VECM). The results indicate that, in the short run, inflation has a significant negative effect on exports, while money supply (M2) has a significant positive effect only in the first lag. Interest rates do not significantly affect exports in the short run. In the long run, inflation exerts a significant negative effect, whereas money supply and interest rates have significant positive effects on exports. Furthermore, the Impulse Response Function (IRF) shows that macroeconomic shocks are temporary and gradually converge to equilibrium, while Forecast Error Variance Decomposition (FEVD) identifies money supply as the largest contributor to export fluctuations. These findings highlight the importance of maintaining monetary stability to support Indonesia’s export performance and international competitiveness.